(untitled) (ESMAT Magazine, 2022)
The increase of criminality in Mexico is intended to be solved with new laws and reforms to the penal norms apparently protective of human rights. However, the adoption and regulation of figures such as organized crime, the official pre-trial detention and the increase of penalties, reflect more of a criminal law of an authoritarian state.